A Study of the Training Load of Chinese Men Cross-Country Skiers in the Winter Olympic - Peng Bai,; Bei Zhang,; Yaping Zhong, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study examines the training load and performance of Chinese male cross-country skiers in preparation for the 2022 Winter Olympics. The research aims to establish a solid foundation for organising training loads and managing competitive readiness in Chinese cross-country skiing competitions. The study used quantitative data from four Chinese male athletes during the preparation period for the Beijing Winter Olympic Games in 2021. The Garmin 945 heart rate monitor was used to observe and document the training load, including factors such as training content, duration, distance, intensity level, and timing. The index test method was employed to assess the athletes' blood index at biweekly intervals. The Chinese skiers underwent a general preparation period that lasted 164 days, a special preparation period that lasted 70 days, and a pre-competition period that lasted 26 days. The overall training volume exceeded that of world-class athletes, with a notable emphasis on terrestrial training. The prevalence of endurance training was lower in comparison to world-class athletes, with a greater emphasis on strength training. The training intensity exhibited a modest increase, with a distribution pattern of low, medium, and high levels of intensity. The frequency of training and land training declined from the general preparation period to the pre-competition period, while the frequency of snow training increased. The intensity of the competition arrangement during the special preparation period was heightened.